Money Matters! Evidence From a Survey Experiment on Attitudes Toward Maternal Employment Across Contexts in Germany - Corinna Frodermann; Lena Hipp; Mareike Bünning (Gender & Society, 2024)
This paper examines the context dependency of attitudes toward maternal employment. We test three sets of factors that may affect these attitudes—economic benefits, normative obligations, and child-related consequences—by analyzing data from a unique survey experimental design implemented in a large-scale household panel survey in Germany (17,388 observations from 3,494 respondents). Our results show that the economic benefits associated with maternal employment are the most important predictor of attitudes supporting maternal employment. Moreover, we find that attitudes toward maternal employment vary by individual, household, and contextual characteristics (in particular, childcare quality). We interpret this variation as an indication that negative attitudes toward maternal employment do not necessarily reflect gender essentialism; rather, gender role attitudes are contingent upon the frames individuals have in mind.
Keywords: 300; maternal employment; factorial survey design; gender role attitudes; survey experiments; work and family; gender norms